The Rise of Socially Responsible Investment Funds: The Paradoxical Role of the Financial Logic - Yan, Shipeng; Ferraro, Fabrizio; Almandoz, Juan (John) (Administrative Science Quarterly, 2019)
Socially responsible investing (SRI) is gaining traction in the financial sector, but it is unclear whether the dominant financial logic complements or competes with the social logic in the founding of SRI funds. Based on insights we gained from observation at an Asian SRI industry association, interviews with SRI professionals in the U.S. and Europe, and other fieldwork, we questioned explanations for SRI’s conflicted relationship with the financial logic. Our observations prompted us to build a panel database of SRI fund foundings from 1970 to 2014 in 19 countries so that we could examine how a dominant logic interacts with alternative logics to promote or stifle institutional change. We decomposed the financial logic into interdependent dimensions as the provider of means (resources, practices, and knowledge) for novel financial ventures to be founded and the enforcer of profit-maximizing ends that constrain such foundings. Our theory suggests a paradoxical role for the financial logic, which explains an intriguing empirical finding: the founding of SRI funds has a curvilinear, inverted-U-shaped relationship with the prevalence of the financial logic. We propose and find that the relationship between the dominant financial logic and the social logic of SRI shifts from complementary to competing as the financial logic becomes more prevalent in society and its profit-maximizing end becomes taken for granted. We examined how certain alternative logics—those of unions, religion, and green political parties—moderate these effects. Our results shed light on how and to what extent institutional change can occur in fields in which one institutional logic is dominant. They also reveal country-level institutional factors that drive SRI.